MEMBANGUN KESADARAN ETIKA LINGKUNGAN KEPADA ANGGOTA JEMAAT GMIM ALFA OMEGA KUMARAKA DALAM YANG TINGGAL DI DAERAH RAWAN BANJIR DENGAN TINGKAT KESADARAN MENJAGA LINGKUNGAN YANG MINIM - Walukow, Gracella (DELAHA: Journal of Theological Sciences, 2025)
Nature, as a living environment, has been gifted to us by God to be used and exploited for human well-being. Humans are far from aware of the importance of environmental preservation. The low level of environmental awareness among the GMIM Alfa Omega Kumaraka Dalam congregation, who live in a flood-prone area, exacerbates flooding, causing losses for those affected. The environment is increasingly damaged by irresponsible human actions. Using a qualitative research method with a descriptive approach, the researcher described what was seen, heard, felt, and asked through direct and indirect observations and interviews. Through this research, the researcher found a lack of dedicated attention from the church to congregations with minimal environmental awareness. Pastors focused too much on providing advice through sermons during services, but lacked a dedicated approach to the congregation. Visits to provide pastoral care to the congregation were rare. The church must be able to fulfill its duties and responsibilities to serve the congregation by maximizing assistance to those with minimal environmental awareness so that the church can guide, support, heal, restore, nurture, and strengthen the lives of the congregation in all aspects of their lives.